A study of price evolution in online toy market - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2010)
We study and contrast pricing and price evolution of online only (Dotcom) and online branch of multi-channel retailers (OBMCRs) based on two panel data sets collected from online toy markets. Panel data regression analyses reveal several interesting empirical results: over time, OBMCRs and Dotcoms charge similar prices on average but Dotcoms significantly increase their shipping costs that eventually drive the overall average price of Dotcoms higher than that of OBMCRs. Price dispersions of both types of retailers are persistent. The price dispersion of OBMCRs is higher than that of Dotcoms at the beginning and does not change much over time, but the price dispersion of Dotcoms increases significantly over time, indicating that the latter will eventually be higher than the former. Moreover, the OBMCRs charge significantly different prices, but the Dotcoms charge similar prices.